1999
DOI: 10.1080/0729436990180105
|View full text |Cite
|
Sign up to set email alerts
|

What the Student Does: teaching for enhanced learning

Abstract: Many teachers see major difficulties in maintaining academic standards in today's larger and more diversified classes. The problem becomes more tractable if learning outcomes are seen as more a function of students' activities than of their fixed characteristics. The teacher's job is then to organise the teaching/learning context so that all students are more likely to use the higher order learning processes which "academic" students use spontaneously. This may be achieved when all components are aligned, so t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
934
0
65

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,198 publications
(1,112 citation statements)
references
References 13 publications
24
934
0
65
Order By: Relevance
“…This would imply a major setback in quality, to the extent that the implication and degree of autonomy of the student are key factors in good learning outcomes (see, for example, Biggs andTang, 1999 or Ramsden, 2003). On the other hand, students may feel that they have the right to determine how they should be taught or assessed: "I'm not going to pay someone who expects me to learn all this stuff by myself" was the recent response in our institution to a lecturer who asked students to go to the computer lab to become familiar with a program (Bay and Daniel, 2001, p. 6).…”
Section: Student-customer Satisfaction: the New Priority Focus Of Polmentioning
confidence: 99%
“…This would imply a major setback in quality, to the extent that the implication and degree of autonomy of the student are key factors in good learning outcomes (see, for example, Biggs andTang, 1999 or Ramsden, 2003). On the other hand, students may feel that they have the right to determine how they should be taught or assessed: "I'm not going to pay someone who expects me to learn all this stuff by myself" was the recent response in our institution to a lecturer who asked students to go to the computer lab to become familiar with a program (Bay and Daniel, 2001, p. 6).…”
Section: Student-customer Satisfaction: the New Priority Focus Of Polmentioning
confidence: 99%
“…Such a student-centered, collaborative, learning strategy [can] transform students from being passive, teacher-dependent, uncritical recipients and reproducers of information into engaged, questioning, reflective and autonomous learners. (Gardiner, 1996, p. 2) Clearly then, student-centered and collaborative Writing Center tutoring practices would be required in a constructively-aligned curriculum (Biggs, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…If tutors are able to adopt approaches that are in keeping with these understandings and values, then they will contribute to a constructively-aligned curriculum, with components addressing the same agenda and supporting each other (Biggs, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This constructive alignment has also been found to be associated with greater frequency of the deep approach and in turn, higher quality student learning (Biggs, 1999). Research has shown that students' perceptions of alignment in teaching are a good indicator of this construct and are similarly associated with the deep approach to learning (Parpala et al, 2010).…”
Section: Overview Of Learning and Course Perception Constructsmentioning
confidence: 95%